2001
DOI: 10.1002/rcm.268
|View full text |Cite
|
Sign up to set email alerts
|

On the fragmentation pathway of the ionized enol of glycine in the gas phase

Abstract: Density functional and second-order many body perturbation approaches were used to compute the potential energy surface for the fragmentation of the ionized enol of glycine [H2NCH = C(OH)2]+* into water and aminoketene radical cation [H2N-HC = CO]+*. Two possible pathways were considered. The potential energy surfaces obtained are very similar and both predict the existence of a molecular complex in which the water is coordinated to the aminoketene moiety in two different fashions with a noticeable binding ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…As an extension to the above study, our previous work located the related transition states with the corresponding activation energies for the fragmentation reactions of the C R bond breaking from the glycine radical cation. 26 Both Simon et al 24 and our pervious work 26 found that the dominate fragment is the immonium ion CH 2 NH 2 + by abstracting the COOH, which is consist with the experimental results. 20,23 Rodriguez-Santiago et al 22 focused only on fragmentation reaction pathways involving intramolecular proton transfers.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…As an extension to the above study, our previous work located the related transition states with the corresponding activation energies for the fragmentation reactions of the C R bond breaking from the glycine radical cation. 26 Both Simon et al 24 and our pervious work 26 found that the dominate fragment is the immonium ion CH 2 NH 2 + by abstracting the COOH, which is consist with the experimental results. 20,23 Rodriguez-Santiago et al 22 focused only on fragmentation reaction pathways involving intramolecular proton transfers.…”
Section: Introductionsupporting
confidence: 68%
“…It is consistent with the results found by Polce and Wesdemiotis. 23 The previous studies 23,24 also indicate that the enol form of the glycine cation radical favors losing water and generating an aminoketene radical cation, but there is no meaningful signal of m/z 41 observed in the spectrum of study of Vorsa et al 20a 3.9 Forming [HCNH + (m/z 28) + CHO + H 2 O] and [HCNH + (m/z 28) + CH(OH) 2 ]. The formation of HCNH + , CHO, and H 2 O from conformer I requires at least the transfer of two protons into the carboxyl acid group, that is, one from the amine group and the other from the methylene group, as well as the breakage of the C-C bond.…”
Section: XIVmentioning
confidence: 82%
See 1 more Smart Citation
“…38 Indeed, the mass spectra of Gly + are quite different from those of the singly charged dienol isomer because in the latter case, the loss of neutral water is the dominant channel. 39,40 In contrast, the calculated PES for the doubly charged glycine shows that both isomers can be directly obtained from Gly 2+ without energy barriers. This is confirmed by the observation of these conformers in the molecular dynamics simulations.…”
mentioning
confidence: 86%
“…However, the transition states connecting them lie above the lowest fragmentation channel of Gly + (NH 2 CH 2 + /COOH); thus, the isomerization processes are not accessible channels in singly charged glycine . Indeed, the mass spectra of Gly + are quite different from those of the singly charged dienol isomer because in the latter case, the loss of neutral water is the dominant channel. , In contrast, the calculated PES for the doubly charged glycine shows that both isomers can be directly obtained from Gly 2+ without energy barriers. This is confirmed by the observation of these conformers in the molecular dynamics simulations.…”
mentioning
confidence: 95%